Age estimation for disorder characterization from pediatric polysomnograms - Festag, Sven; Herberger, Sebastian; Spreckelsen, Cord; Krefting, Dagmar; Fietze, Ingo; Penzel, Thomas; Marschik, Peter B.; Spicher, Nicolai (Biomedical signal processing and control, 2025)
Estimating biological age via deep neural networks (DNNs) processing polysomnograms (PSGs) showed promising results in adults. While age estimation it…